Відповідальність за невиконання або неналежне виконання зобов’язання подружжя по утриманню - Красвітна, Т. П.; Krasvitna , T. P. (Європейські перспективи. - 2018. - №3. - С. 116-122, 2018)
Розкрито проблемні питання відповідальності за невиконання або неналежне виконання зобов’язання подружжя по утриманню. Визначено заходи відповідальності за невиконання та (або) неналежне виконання зобов’язання подружжя по утриманню за сімейним законодавством України та надано пропозиції з удосконалення чинного сімейного законодавства України у цій сфері.

The author of the article has revealed the problematic issues concerning the liability for the failure or improper performance of spouses’ obligations for support. Recovery of alimony for support of one of the spouses is the way of protecting the violated family rights and interests, but it is not a measure of liability. The author has analyzed the court practice for the application of family law of Ukraine regarding the cases on disputes about the recovery of a penalty (fine) for alimony in arrears to support one of the spouses. It has been substantiated that the penalty (fine) for alimony in arrears as a measure of liability is applied to the recovery of alimony to support one of the spouses in case of the delay in payment. The penalty (fine) for alimony in arrears to support one of the spouses may be recovered, if one of the spouses was obliged to pay the alimony both by the court decision and by the agreement between the spouses. It has been proved that the agreement between the spouses on the provision of support, the marriage contract, may provide the penalty (fine) for alimony in arrears to support one of the spouses on the basis of the notary’s executive order. It has been argued that the compensation for damages, compensation for moral harm, the recovery of the inflation index during the alimony in arrears, the recovery of three percent per annum of the overdue amount as a measure of liability can not be applied for the violation of spouses’ obligation for support; the agreement between the spouses may provide the use of such forms of liability for alimony in arrears. The author has offered to make amendments into the Family Code of Ukraine and to eliminate restrictions in the application of such a method of protection as compensation for material and moral harm caused by the violation of family rights and interests.

Раскрыты проблемные вопросы ответственности за неисполнение или ненадлежащее исполнение обязательства супругов по содержанию. Определены меры ответственности за неисполнение и (или) ненадлежащее исполнение обязательства супругов по содержанию по семейному законодательству Украины и предоставлены предложения по усовершенствованию действующего семейного законодательства Украины в этой сфере.
Keywords: подружжя; зобов’язання; утримання; аліменти; відповідальність; збитки; моральна шкода; spouse; commitment; maintenance; alimony; liability; damages; moral damage; супруги; обязательства; содержание; алименты; ответственность; ущерб; моральный вред